Biography, historiography, and modes of philosophizing : the tradition of collective biography in early modern Europe - Baker, Patrick, 1976- (Renaissance Society of America texts and studies series, 2017)
"By way of essays and a selection of primary sources in parallel text, Biography, Historiography, and Modes of Philosophizing provides an introduction to a vast, significant, but neglected corpus of early modern literature: collective biography. It focuses especially on the various related strands of political, philosophical, and intellectual and cultural biography as well as on the intersection between biography, historiography, and philosophy. Individual texts from the fifteenth to the eighteenth century are presented as examples of how the ancient collective biographical tradition--as represented above all by Plutarch, Suetonius, Diogenes Laertius, and Jerome--was received and transformed in the Renaissance and beyond in accordance with the needs of humanism, religious controversy, politics, and the development of modern philosophy and science"--Provided by publisher.